2018
DOI: 10.1080/09638288.2018.1473508
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported experiences of using community rehabilitation and/or support services whilst living with a long-term neurological condition: a qualitative systematic review and meta-aggregation

Abstract: Patient reported experiences identified common factors associated with process quality (respect, choice, autonomy, information provision, communication) and activities of patient centered care (personalized care, shared decision-making, self-management support) despite heterogeneity of neurological conditions, service configurations, and geographical location. These factors impact quality of life. Implications for Rehabilitation Patient reported experiences provide useful information about courtesy, respect, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 108 publications
(155 reference statements)
1
13
0
2
Order By: Relevance
“…According to Bandura (1997), self-efficacy beliefs influence an individual’s actions, effort, and resilience when faced with obstacles and failure, as well as the amount of stress and depression experienced during times of difficulty [ 47 ]. Outcomes of self-efficacy have been found to be very important for people with long-term neurological conditions; therefore, activities facilitating self-efficacy are valuable additions to community rehabilitation [ 48 ]. The value of horseback riding in building self-efficacy is well recognised and has been studied in various settings [ 17 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Bandura (1997), self-efficacy beliefs influence an individual’s actions, effort, and resilience when faced with obstacles and failure, as well as the amount of stress and depression experienced during times of difficulty [ 47 ]. Outcomes of self-efficacy have been found to be very important for people with long-term neurological conditions; therefore, activities facilitating self-efficacy are valuable additions to community rehabilitation [ 48 ]. The value of horseback riding in building self-efficacy is well recognised and has been studied in various settings [ 17 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in accessing services and healthcare professionals may also reflect problems in the structure and coordination of care services for FND and LTNCs in general, as a significant proportion of people with FND reported a lack of coordination between services in planning their care. Jackson et al (51) found that people with LTNCs viewed coordination between services as vital in ensuring that there is a continuity of care within community settings, but that they often experienced limited access to these services. Since FND is often managed within community settings and requires multidisciplinary treatment (14), it is thus vital to have coordination between different services which should include, for many patients, a coordination between community neurotherapy and community mental health services.…”
Section: Difficulties Accessing Services and Supportmentioning
confidence: 99%
“…Введение в Израиле закона об обязательном государственном медицинском страховании в 1995 г. привело к возникновению необходимости контроля качества реабилитации с целью оптимизации бюджета, выделенного Больничными кассами на восстановление пациентов [5] [17,18]. Оценка качества лечения с точки зрения пациента и членов его семьи выполняется ежегодно методом стандартного опросника, проводимого выборочно независимыми компаниями также по общепринятым принципам [16,19]. Внешняя инспекция и контроль качества реабилитации проводятся в Израиле профессиональной командой Больничных касс.…”
Section: подходы принципы и формы оценки качества реабилитацииunclassified
“…Постоянный контакт с пациентом, своевременная передача профессиональной информации и обсуждение динамики и целей проводимой программы происходят постоянно в большинстве реабилитационных структур [21]. Оценка эффективности участия пациента и его семьи в процессе реабилитации является важным показателем качества и обычно оценивается методом опросников пациентов и членов семей, проводимых ежегодно в Израиле [16,19]. В отделении реабилитации Медицинского центра «Сорока» пациент вместе с членом его семьи активно приглашается на встречу с врачом-реабилитологом дважды в течение госпитализации -сразу после первого обсуждения на заседании команды и после заседания, в ходе которого принято решение о выписке пациента на амбулаторное лечение.…”
Section: индикаторы качества процесса реабилитацииunclassified